Sulfide Stress Cracking Behavior of a Martensitic Steel Controlled by Tempering Temperature - Sun, Yu (Materials (Basel), 2018)
A medium-carbon Cr–Mo–V martensitic steel was thermally processed by quenching (Q) at 890 °C and tempering (T) at increasing temperatures from 650 °C to 720 °C and the effect of tempering temperature, T(t), on sulfide stress cracking (SSC) behaviors was estimated mainly via double cantilever beam (DCB) and electrochemical hydrogen permeation (EHP) tests and microstructure characterization. The results indicate that the threshold stress intensity factor for SSC, K(ISSC), increased with increasing T(t). The overall and local H concentration around the inclusions decreased with increasing T(t), due to reductions in the amounts of solute atoms, grain boundaries and dislocations, which effectively prevented SSC initiation. Also, increasing T(t) caused an increased fraction of high-angle boundaries, which evidently lowered the SSC propagation rate by more frequently diverting the propagating direction and accordingly restricted SSC propagation. The overall SSC resistance of this Q&T–treated steel was therefore significantly enhanced.